Accomplishment of Waterfall Model Exhausting Agile Data Science (Global Journal of Computer Science and Technology, 2022)
Agile information science is an technique to information technology targeted around net utility improvement It asserts that the handiest output of the information technological know-how procedure appropriate for effecting alternate in an organization is the net application It asserts that application development is a essential talent of a facts scientist consequently doing data science will become approximately constructing applications that describe the applied research procedure speedy prototyping exploratory data analysis interactive visualization and applied system gaining knowledge of